Potensi Senyawa Betalain pada Ekstrak Biji Binahong Berbatang Merah (Anredera cordifolia) sebagai Fotosensitizer Dye Sensitized Solar Cell (DSSC) - Nafisa Cahyani; I Gusti Made Sanjaya (Al-Kimia, 2021)
Abstract: This study aims to examine the extract of red trunk binahong seed as a dye in Dye Sensitized Solar Cell (DSSC). (Anredera cordifolia) characterization was carried out by UV-Visible spectrophotometry and resulted in absorption at a wavelength of 537 nm, purification the extract of red trunk binahong seed was carried out by column chromatography using methanol: ethyl acetate as  solvent with ratio of 3: 2 and 10 fractions color were produced. The identification of compounds and functional groups were analyzed by FTIR which showed the presence of betalain derivatives, namely betanidine, betanine, and neobetanin. Molecular weight analysis was carried out by LC-MS and the molecular weight of betanidine was 386.3171. The voltage and current from the DSSC results were measured using  multimeter, the efficiency of the extract of red trunk binahong seed was 0.64% and the one that experienced a change in color to orange was 0.55%.Keywords:, betalain, betanidine, betanine, DSSC, red trunk binahong